Os acromiale: a review of its incidence, pathophysiology, and clinical management. Issue 8 (August 2019) - Hurst, Simon A.; Gregory, Thomas M.; Reilly, Peter
Abstract : An os acromiale occurs when any of the primary ossification centres of the acromion fail to fuse with the basi-acromion. It is present in approximately 8% of individuals, and whilst the majority of these individuals are unaffected it can cause significant pain and disability. It can impact seemingly unrelated surgical intervention in the region such as subacromial decompression and reverse shoulder arthroplasty. A painful os acromiale can be both a diagnostic challenge, and difficult to manage. There remain a wide variety of surgical practices with variable outcomes achieved. We present an evidence-based discussion of the surgical techniques described to date in the literature, alongside a comprehensive review of the incidence and pathophysiology of os acromiale. This review was written after a comprehensive analysis of the literature to date relating to os acromiale. Particular focus was given to material examining surgical management techniques, and the condition's incidence across different population groups. Open reduction and internal fixation using cannulated screws, or tension band wiring have superior outcomes in the literature in the treatment of symptomatic os acromiale. There may be a biomechanical advantage of combining the two techniques. Preservation of large anterior deltoid attachment is necessary, with consideration being given to the local blood supply. There is likely no additional benefit from iliac crest vs local bone grafting. Research in this area remains of a low evidence level with small samples sizes. Appropriately powered clinical research of a higher-level evidence methodology is needed in order to differentiate further in the choice of surgical intervention. Cite this article: EFORT Open Rev 2019;4:525-532. DOI: 10.1302/2058-5241.4.180100